2020
DOI: 10.1111/acel.13221
|View full text |Cite
|
Sign up to set email alerts
|

GSK3‐ARC/Arg3.1 and GSK3‐Wnt signaling axes trigger amyloid‐β accumulation and neuroinflammation in middle‐aged Shugoshin 1 mice

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…Wnt signaling pathways are critical in the pathogenesis of the AD (Vallée & Lecarpentier, 2016; Vallée et al, 2018). Wnt signaling pathway can regulate oxidative stress, inflammation, and apoptosis (Ali et al, 2020; Caricasole et al, 2004; Godoy et al, 2014; Rao et al, 2020; Sinha et al, 2015; Vallée et al, 2017; Yao et al, 2015; Yu et al, 2020). GSK‐3β is a dynamic and omnipresent serine/threonine‐protein kinase (Xu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Wnt signaling pathways are critical in the pathogenesis of the AD (Vallée & Lecarpentier, 2016; Vallée et al, 2018). Wnt signaling pathway can regulate oxidative stress, inflammation, and apoptosis (Ali et al, 2020; Caricasole et al, 2004; Godoy et al, 2014; Rao et al, 2020; Sinha et al, 2015; Vallée et al, 2017; Yao et al, 2015; Yu et al, 2020). GSK‐3β is a dynamic and omnipresent serine/threonine‐protein kinase (Xu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Example, recently it was shown that mutations of SGO2 (frameshift, p.Glu485Lysfs*5) and CLDN14 collectively cause coincidental Perrault syndrome which is a rare autosomal genetic disorder characterized by sensorineural hearing loss (SNHL) in males and females and ovarian dysfunction in females [71,72]. Some of the studies in last few years also showed the involvement of shugoshin in neurological disorders like late-onset Alzheimer's disease (LOAD) [73,74]. It is important to mention that not all the diseased conditions are due to chromosome instability, which is induced by impaired shugoshin function of centromeric cohesion.…”
Section: Shugoshin In Other Clinical Disordersmentioning
confidence: 99%
“…For example, recently it was shown that mutations of SGO2 (frameshift, p.Glu485Lysfs *5) and CLDN14 collectively cause coincidental Perrault syndrome, which is a rare autosomal genetic disorder characterized by sensorineural hearing loss (SNHL) in males and females and ovarian dysfunction in females [71,72]. Some studies in the last few years also showed the involvement of shugoshin in neurological disorders such as late-onset Alzheimer's disease (LOAD) [73,74]. It is important to mention that not all the diseased conditions are due to chromosome instability, which is induced by impaired shugoshin function of centromeric cohesion.…”
Section: Shugoshin In Other Clinical Disordersmentioning
confidence: 99%